2020
DOI: 10.3389/fmicb.2020.560474
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Epidemiology of Extended-Spectrum β-Lactamase-Producing Multidrug-Resistant Klebsiella pneumoniae From Red Kangaroo, China

Abstract: Due to its drug resistant nature, β-lactamase represents a serious challenge for public health. Extended-spectrum β-lactamase (ESBL) producing Klebsiella pneumoniae clones are increasingly reported worldwide. Little is known about the prevalence and biological characteristics of drug-resistant strains in zoos. During routine surveillance at the Zhengzhou Zoo of China, we found Klebsiella pneumoniae isolate in healthy Red Kangaroos ( Macropus Rufus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…The isolation of the widespread healthcare associated clone ST307 from companion animals, the recovery of highly virulent strains from dogs, and the putative transmission of strains and plasmids between humans and invertebrates in the hospital environment are pertinent examples. Combined with multiple examples from the literature [59][60][61][62][63] , our data therefore underlines the importance of basic hygiene measures, particularly with respect to contact with animals.…”
Section: Discussionsupporting
confidence: 62%
“…The isolation of the widespread healthcare associated clone ST307 from companion animals, the recovery of highly virulent strains from dogs, and the putative transmission of strains and plasmids between humans and invertebrates in the hospital environment are pertinent examples. Combined with multiple examples from the literature [59][60][61][62][63] , our data therefore underlines the importance of basic hygiene measures, particularly with respect to contact with animals.…”
Section: Discussionsupporting
confidence: 62%
“…Klebsiella sp. isolates were isolated and collected from 2018 to 2020 ( Wang et al, 2020 ) and preserved in the laboratory, from which 56 Klebsiella sp. isolates were selected, including 21 isolates from fresh fecal samples of animals and 35 isolates from human clinical samples ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…and IncFIB KN plasmid replicons in four ESBL-K. pneumoniae isolates tested. Previous studies showed the presence of K. pneumoniae isolates harboring bla CTX-M-14 located on IncFIB K and IncFII K obtained from healthy red kangaroos (Wang et al, 2020) and from a clinical isolate in China (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%